Determination of Merremia cissoids leaf area using the linear measures of the leaflets - doi: 10.4025/actasciagron.v33i3.6379 - Carvalho, Leonardo Bianco (2011)
Knowledge of the weed leaf area may give support to study the interference relationships between weeds and crops. The objective of this research was to determine a mathematical equation for M. cissoides leaf area estimation based on the relationship between the leaf blade linear measures. Leaves of the species were collected from a variety of agroecosystems at São Paulo State University, Jaboticabal, São Paulo State, Brazil, measuring the length (L), maximum width (W) and real leaf blade area of the three kinds of leaflets. Linear equations Y = a x (X) were estimated for each kind of leaflet. The confidence intervals of the primary leaflet equation overlapped those ones from the secondary leaflet equation, and then only one equation was considered for these leaflets. So, an equation of principal leaflet plus that one of primary + secondary leaflets were used to determine the M. cissoides leaf area. Thus, the leaf area of the species might be determined by the sum of the leaf areas of the principal leaflet with the primary + secondary leaflets, according to the equation LAest = 0.501 x (X) + 2.181 x (Z), where X indicates L x W of the principal leaflet and Z indicates medium L x W of the primary + secondary leaflets, respectively.